2020
DOI: 10.2147/opth.s270690
|View full text |Cite
|
Sign up to set email alerts
|

<p>Safety and Efficacy of a New Posterior Chamber Phakic Intraocular Lens in Cases of High Myopia: Early Results</p>

Abstract: Purpose: To demonstrate the visual outcomes of a foldable, hydroxy ethyl-methacrylate, single-piece, posterior chamber phakic intraocular lens (pIOL). Study Type: Retrospective study. Materials and Methods: Patients presenting with moderate to high myopia who underwent surgical correction with a posterior chamber phakic IOL (refractive intraocular lens, phakic intraocular lens, Appasamy Associates, Chennai, India) were retrospectively reviewed. Only patients with at least one-year follow-up were included. Mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…The results showed that the two groups had a similar predictive performance, indicating that the implantation of the EVO-ICL in patients with short WTW corneal diameters had good predictability. This was similar to the finding of a previous study involving normal WTW patient ( 2 , 3 , 12 14 ).…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that the two groups had a similar predictive performance, indicating that the implantation of the EVO-ICL in patients with short WTW corneal diameters had good predictability. This was similar to the finding of a previous study involving normal WTW patient ( 2 , 3 , 12 14 ).…”
Section: Discussionsupporting
confidence: 92%
“…It is reported that the lowest rate of endothelial cell loss after non-central hole ICL was 1.1% and the highest was 13.4% within 5 years [100,101]. Beyond five years after operation, the lowest rate was 4.7% and the highest was 19.75% [102][103][104][105][106].…”
Section: Loss Of Corneal Endothelial Cells and Corneal Decompensationmentioning
confidence: 99%
“…The correction range is wide and does not involve limiting the corneal thickness; therefore, it has been widely used in clinical practice [5][6][7]. Since the advent of clinical application of EVO ICL, several short-term studies [8][9][10][11] have confirmed its safety, efficacy, predictability, and stability in correcting HM. However, doctors and patients are concerned about its long-term safety, efficacy, and stability.…”
Section: Introductionmentioning
confidence: 99%